2019
DOI: 10.2196/mhealth.9904
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Using an App in HIV Patients Older Than 60 Years: Pilot Program

Abstract: BackgroundNew technologies can promote knowledge of HIV infection among patients suffering from this disease. Older patients with HIV infection represent an increasingly large group that could benefit from the use of specific apps.ObjectiveThe aim of the study was to observe the acceptability and use of a mobile app on HIV infection in patients at least 60 years old and offer them the possibility of anonymously establishing contact with their peers.MethodsA series of clinical and psychosocial parameters were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…There is scant literature on the acceptability of a ready-made, commercially available mHealth platform for addressing ART adherence. Further, there are scant data on PLWH aged above 55 years who may not be as likely to own smartphones and may have limitations to data and internet access [29,30]. Therefore, today’s inclusive mHealth platforms also need to include SMS messaging (texting) in partnership with apps that require internet access in order to reach vulnerable populations, known as “biprogrammatic”; we define this term as an app program that functions with both smartphone and texting-only (ie, feature or “flip” phone) platforms.…”
Section: Introductionmentioning
confidence: 99%
“…There is scant literature on the acceptability of a ready-made, commercially available mHealth platform for addressing ART adherence. Further, there are scant data on PLWH aged above 55 years who may not be as likely to own smartphones and may have limitations to data and internet access [29,30]. Therefore, today’s inclusive mHealth platforms also need to include SMS messaging (texting) in partnership with apps that require internet access in order to reach vulnerable populations, known as “biprogrammatic”; we define this term as an app program that functions with both smartphone and texting-only (ie, feature or “flip” phone) platforms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of nonquantitative or nonexperimental studies were conducted to investigate the nature of optimal interventions. These are summarized in Table 2 [71][72][73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Higher-income Countries Groupmentioning
confidence: 99%
“…Design-related studies indicated the themes that interventions should be customizable, provide disease information, and maintain confidentiality [71][72][73][74][75][76][77][78][79][80][81][82][83][84]. A reminder intervention seems to be acceptable in the patients studied [76,77,80,82].…”
Section: Higher-income Countries Groupmentioning
confidence: 99%
“…Recently, there has been mounting evidence of the feasibility of smartphone apps in remote monitoring and flexible follow-up of patients in western countries [8-10]. However, the experience of using a smartphone app in the management of chronic diseases in China is limited.…”
Section: Discussionmentioning
confidence: 99%